2018
DOI: 10.1039/c8nj03112f
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical functionalized biodegradable PLA electrospun nanofibrous membrane with superhydrophobicity and antibacterial properties for oil/water separation

Abstract: A hierarchical surface-modified biodegradable electrospun nanofibrous PLA membrane showed excellent superhydrophobicity and antibacterial properties for high-efficient oil/water separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Definitely, the porous morphology of the patch surface also plays a major role for wetting behavior. For instance, Liu et al showed that the WCA of pristine PLA was 129.2° when it is prepared in the form of randomly grown nanofibers [ 30 ]. The Cassie–Baxter model suggests that an indistinctly hydrophobic material gets more hydrophobic with the increasing roughness [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Definitely, the porous morphology of the patch surface also plays a major role for wetting behavior. For instance, Liu et al showed that the WCA of pristine PLA was 129.2° when it is prepared in the form of randomly grown nanofibers [ 30 ]. The Cassie–Baxter model suggests that an indistinctly hydrophobic material gets more hydrophobic with the increasing roughness [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such materials were shown to have excellent bacterial antiadhesion characteristics against both E. coli O157:H7 and S. aureus . Similar nanoporous structures can also be prepared by electrospinning process, which is more commonly used for organic and polymeric materials (Liu & Yuan, 2018; Ma et al., 2005).…”
Section: Superhydrophobic Antifouling (Anticontact) Surfacesmentioning
confidence: 99%
“…The modified nanofiber membranes can separate oil and water with an efficiency of 99% simply using gravitational force as shown in Figure 11. [50,81] Similarly, by incorporating polydopamine, silver nanoparticles, [82] and β-cyclodextrins [83] on PLA nanofibers increased the hydrophobicity and permeation fluxes for a wide variety of oils and a desirable separation performance of ≈95%.…”
Section: Other Pollutantsmentioning
confidence: 99%